2015
DOI: 10.3389/fncel.2015.00089
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of repetitive firing and synchronous network activity in neocortical interneurons by inhibition of A-type K+ channels and Ih

Abstract: GABAergic interneurons provide the main source of inhibition in the neocortex and are important in regulating neocortical network activity. In the presence 4-aminopyridine (4-AP), CNQX, and D-APV, large amplitude GABAA-receptor mediated depolarizing responses were observed in the neocortex. GABAergic networks are comprised of several types of interneurons, each with its own protein expression pattern, firing properties, and inhibitory role in network activity. Voltage-gated ion channels, especially A-type K+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 148 publications
(223 reference statements)
4
28
1
Order By: Relevance
“…6A; Table 1), confirming a previous report that 4AP can cause a broadening of neuronal action potentials (Mitterdorfer and Bean, 2002). We concluded that 4AP affects PV-interneuron firing more than it does SST and pyramidal firing, leading to a preferential activation of the PV cell class, supporting previous findings which were not performed in the blockade of both glutamatergic and GABAergic currents (Williams and Hablitz, 2015). PV interneurons are, thus, likely to be the main source of the persistent pathological discharges following application of glutamate receptor blockers, in this model.…”
Section: Ap Preferentially Activates Pv Interneuronssupporting
confidence: 91%
“…6A; Table 1), confirming a previous report that 4AP can cause a broadening of neuronal action potentials (Mitterdorfer and Bean, 2002). We concluded that 4AP affects PV-interneuron firing more than it does SST and pyramidal firing, leading to a preferential activation of the PV cell class, supporting previous findings which were not performed in the blockade of both glutamatergic and GABAergic currents (Williams and Hablitz, 2015). PV interneurons are, thus, likely to be the main source of the persistent pathological discharges following application of glutamate receptor blockers, in this model.…”
Section: Ap Preferentially Activates Pv Interneuronssupporting
confidence: 91%
“…This hypothesis proposes that synchronous activation of inhibitory interneurons 515 (the "initial step" investigated here) gives rise to a strong inhibitory signal that 516 activates the excitatory, pyramidal cell population via PIR [12] (see Fig 1). As 517 experimental support for this theory accumulates [1,[8][9][10][11][12][13], computational insights such 518 as those presented here can provide further support for its viability by proposing synchrony and predominantly GABAergic IIS [29,51], and thus 4-AP is a commonly 526 used epilepsy model [31,32]. This experimental evidence justifies not only the use of has also been shown to underlie IIS in the in vivo pilocarpine model of epilepsy [13], 531 precede seizures in both the low-Mg, high K+ model [26,28] and electrical stimulation 532 models of seizure initiation [52], and more generally precede seizures in rodents [9,29].…”
mentioning
confidence: 75%
“…125 The rest of the parameter values (a, b, d, k low , k high ) were chosen through a 126 parameter exploration to match the difference in rheobase caused by treatment of Unpublished in-house experiments were used for the rheobase values of control and 128 4-AP interneurons, as recorded in the same cell, given that such details are not available 129 in the existing literature. An increase in spike-frequency adaptation in the 4-AP setting 130 is also implied by the literature [32] and correspondingly influenced the determination of 131 these parameters. As the model of Ferguson et.…”
Section: Neuron Models 92mentioning
confidence: 89%
“…In the current study, we show that mouse NGFCs express Kv4 and auxiliary subunit transcripts that translates to a functional IKA conductance. Although the ramifications of Kv4 channel and auxiliary subunits have been mainly investigated in pyramidal cells, their expression and role in modulating subthreshold membrane dynamics, firing properties and dendritic excitability of IN subtypes have been described 1,65,67,72,74,75,76,77,78,79 . We extend these observations to NGFCs and demonstrate IKA can effectively influence delay to spike and action potential threshold resulting in increased intrinsic excitability similar to that seen in STP-SE ultimately resulting in enhanced dendritic integration.…”
Section: Discussionmentioning
confidence: 99%